الاختلاف في الحكم على الرواة وأثره في دقة المنهج النقدي عند المحدثين - بوقفة، ليلى Bouquffah, Laila; عومار، صالح Oumar, Saleh (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2021)
يتناول هذا المقال مسألة علمية متعلقة باختلاف نقاد الحديث في الحكم على الرواة، وأثر ذلك في دقة منهجهم النقدي وعلميته، وقد درست ذلك من خلال ضبط معنى الاختلاف، ثم بيان أهم الأسباب التي تؤدي إلى اختلاف نقاد الحديث في الحكم على الراوي، سواء كانت متعلقة بطبيعة المنهج أو الناقد أو الراوي، مع بيان أثر هذا الاختلاف على المنهج النقدي الحديثي، حيث إنه اختلاف علمي طبيعي لا يطعن في قواعد النقد الحديثي وأصوله، ولا يعبر عن تناقض مبادئه وأحكامه، بل هو دليل أمانة وعدل وموضوعية، ودقة نقاد الحديث في البحث والحكم على الرواة جرحا وتعديلا.
This article deals with a scientific issue related to the difference of Hadith’s Critics in the Judgment to of the narrators and the impact on the accuracy and scientific. Critical approach of the Hadith. I studied this by controlling the meaning of the difference and the most important reasons that lead to the difference between Hadith Critics in judging the narrators whet her it is related to the approach itself as it is the Critic, or to the narrators. This shows the impact on the Critical approach (Method) of the “Hadith” Since it is a natural scientific difference which does not reflect the contradiction of the principals and rules of the Hadith Critics but an evidence to fairness, probity and objectivity besides the precision or the exactness of “ El hadith” Critics in the search and judgment for and or the narrators and adjustment or adaptation or amendment.
Keywords: القرآن الكريم -- الأحكام الشرعية -- علم الأحاديث -- التراث العربي